2022
DOI: 10.9734/ajee/2022/v17i430296
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Residues in Waste Impacted Surface Waters from Lagos, Nigeria

Abstract: In the past few decades, there has been increasing interest and concern about the environmental presence of human and veterinary pharmaceutically active chemicals (PHACs). and the implication of such on ecosystem health at organismal and population levels This study was conceived, to identify and quantify the concentrations of an important sub-group i.e., the pharmaceuticals. Which have been shown to have ecological implications on various aquatic life-forms. In surface water bodies in Lagos Nigeria. Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It has an antibacterial effect on both gram-negative and positive bacteria. Some reports indicated that DOX occurs in the aquatic environment with residues ranging from 0.11 to 39.5 µg/L at farms in Jiangsu Province, China [9], and <0.05 µg/L in Nigeria [10], 13.62 ng/L in Huangpu River, Shanghai, China [11]. DOX, like some other antibiotics, is stable in the environment and difficult to be biodegraded.…”
Section: Introductionmentioning
confidence: 99%
“…It has an antibacterial effect on both gram-negative and positive bacteria. Some reports indicated that DOX occurs in the aquatic environment with residues ranging from 0.11 to 39.5 µg/L at farms in Jiangsu Province, China [9], and <0.05 µg/L in Nigeria [10], 13.62 ng/L in Huangpu River, Shanghai, China [11]. DOX, like some other antibiotics, is stable in the environment and difficult to be biodegraded.…”
Section: Introductionmentioning
confidence: 99%